2020
DOI: 10.1186/s12894-020-00605-6
|View full text |Cite
|
Sign up to set email alerts
|

Cefaclor as a first-line treatment for acute uncomplicated cystitis: a retrospective single-center study

Abstract: Background: Wide-spectrum antibiotics have been favored to treat acute uncomplicated cystitis (AUC) for a long time, leading to the emergence of multi-drug resistant bacteria. We hypothesize that narrow-spectrum antibiotics might mitigate the issue and aim to investigate the clinical efficacy of cefaclor in patients with AUC. Methods: We retrospectively reviewed the clinical data of female outpatients with AUC treated with cefaclor and evaluated the safety and clinical efficacy. Clinical cure was defined as th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
1
1
Order By: Relevance
“…In our study, more than two-thirds of the isolates (63%) were ESBL-EC. A high prevalence of ESBL-EC strains have been raised quite consistently from previous studies carried out in Morocco ( Lahlou Amine et al., 2009 ; Romli et al, 2011 ; El Bouamri et al., 2014a ; El bouamri et al., 2014b ; Sbiti et al., 2017 ) and outside ( Gravey et al., 2017 ; Critchley et al., 2019 ; Koguchi et al., 2020 ; Tan et al., 2020 ; van Hout et al., 2020 ).…”
Section: Discussionsupporting
confidence: 62%
“…In our study, more than two-thirds of the isolates (63%) were ESBL-EC. A high prevalence of ESBL-EC strains have been raised quite consistently from previous studies carried out in Morocco ( Lahlou Amine et al., 2009 ; Romli et al, 2011 ; El Bouamri et al., 2014a ; El bouamri et al., 2014b ; Sbiti et al., 2017 ) and outside ( Gravey et al., 2017 ; Critchley et al., 2019 ; Koguchi et al., 2020 ; Tan et al., 2020 ; van Hout et al., 2020 ).…”
Section: Discussionsupporting
confidence: 62%
“…Cefaclor showed suboptimal results with 62% sensitivity and with 68.6% sensitivity against E. coli; this in contrast with other studies which reported an overall 94% and 80% sensitivity [ 45 , 46 ]. Cefaclor has a spectrum of activity that resembles that of cephalexin with added activity against β-lactamase-producing Haemophilus influenza [ 47 ].…”
Section: Discussioncontrasting
confidence: 79%
“…Upwards of one-third of the E. coli strains in our investigation (33.48%) were ESBL- E. coli strains. Several earlier investigations [ 20 , 54 , 55 , 56 ] have repeatedly revealed a significant rate of ESBL- E. coli strains. According to Hashemizadeh et al [ 57 ], 41% of outpatients in Kerman, Iran, had ESBL-positive isolates from UTIs.…”
Section: Discussionmentioning
confidence: 99%